Protecting Public Rights on Land Management: A Disjunction between Ideality and Reality (Medico Legal Update, 2021)
Land-use systems are characterized by complex interactions between human decision-makers and theirrights environment. Mismatches between the scale of human drivers and the impacts of human decisionspotentially threaten the public rights as a whole. The research is a normative legal research using a statute,case, and conceptual approaches. The results show that land for management rights can be used for thepurposes of conducting their duties or business, and its use can be transferred to third parties with theapproval of the holder of management right. In fact, transfer of rights and imposition of mortgage rightscan occur even without the permit of the holder of management right. However, when there is default,the creditor experiences obstacles because the National Land Agency rejects to issue a Land RegistrationCertificate without the holder’s permit of management rights, so that collateral cannot be executed. Thiscondition results in the failure to fulfill the principles of justice and legal certainty for creditors and debtors.This provision should be abolished because it contradicts the principle of justice and legal certainty for theparties having an interest in utilizing the management rights land.